Epidemiological Features of Highly Pathogenic Avian Influenza in Cameroon - Marc K. Kouam; Honorine N. Tchouankui; Arouna Njayou Ngapagna (Veterinary Medicine International)
The epidemiology of avian influenza is unknown in Cameroon despite the two outbreaks that occurred in 2006 and 2016-2017, respectively. In order to fill the gap, an attempt was made to provide some basic information on the epidemiology of highly pathogenic avian influenza in Cameroon. Thus, data were collected from follow-up reports of the second HPAI outbreaks prepared by the veterinary health officials of Cameroon and sent to the World Organisation for Animal Health (OIE). Two HPAI virus strains (H5N1 and H5N8) turned out to occur, with H5N1 virus involved in the Center, South, West, and Adamawa regions outbreaks and H5N8 involved in the Far North outbreak only. The affected hosts were the laying hens, backyard chickens, turkeys, guinea fowls, ducks, broiler and layer breeders, and geese for the H5N1 virus and the Indian peafowl (Pavo cristatus), pigeon, ducks, backyard chickens, and guinea fowls for the H5N8 virus. The first outbreak took place in Mvog-Betsi poultry complex in the Center region on the 20th May 2016 and spread to other regions. The mortality rate varied from 8% to 72% for H5N1 virus and was 96.26% for the H5N8 strain in Indian peafowl. No human case was recorded. The potential supporting factors for disease dissemination identified on the field were the following: poultry and eggs dealers moving from one farm, market, or town to another without any preventive care; poor biosecurity measures on farms and live poultry markets. After the first HPAI H5N1 virus outbreak in 2006, the second HPAI outbreak ten years later (2016-2017) involving two virus strains is a cause of concern for the poultry industry. The Cameroon Epidemio-Surveillance Network needs to be more watchful.